An in-depth assessment of convolutional neural networks for rail surface defect detection (Research, Society and Development, 2022)
The consistent monitoring of rails is based on correctly identifying defects to support corrective measures. Recently, convolutional neural networks (CNN), a deep learning method, have been providing outstanding results for the automatic detection of defects. However, several aspects of CNN-based approaches such as network architecture, transfer learning and processing time remains not fully understood. In this work, we performed an in-depth assessment of ten widely used CNN models with the objective of finding the one with the best performance in identifying defects in rail surface images. The classification results are promising, reaching an average accuracy of 83.7% on detection of mild defects and squat. The Inceptionv3 network provided the best results by correctly identifying 92% of images with severe squat defects.